2011
DOI: 10.1111/j.1468-2494.2011.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction of apoptosis, necrosis and genotoxicity by cosmetic preservatives: application of flow cytometry as a complementary analysis by NRU

Abstract: Preservatives are used in cosmetics to prevent microbial contamination; however, some preservatives are not free of allergenic and cytotoxic potential. Allergenicity and cytotoxicity potential values are major aspects of preservative safety, which determine limitations and maximum concentration dose in a cosmetic product. The purpose of this study was to investigate and compare the in vitro apoptosis, necrosis and genotoxicity-inducing potential of five different types of preservatives: Phenoxyethanol (PE), Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…In this way, apoptosis serves as a natural prevention for cancer, and factors that can inhibit apoptotic mechanisms have the potential to enhance risk of cancer development. Parabens have been shown to induce cell death by apoptosis in several cell types in vitro, including in human skin keratinocytes (Handa et al, 2006;Ishiwatari et al, 2007), in human dermal fibroblasts (Carvalho et al, 2012), in human hepatoma HepG2 cells (Khanal et al, 2012) and in rat pheochromocytoma (adrenal) PC12 cells (Egawa et al, 2012). However, all these studies were carried out at high doses of parabens in the 100 μM or above range, which are well above any concentrations measureable in human breast tissue (Barr et al, 2012).…”
Section: Hallmark 3: Resisting Cell Deathmentioning
confidence: 99%
“…In this way, apoptosis serves as a natural prevention for cancer, and factors that can inhibit apoptotic mechanisms have the potential to enhance risk of cancer development. Parabens have been shown to induce cell death by apoptosis in several cell types in vitro, including in human skin keratinocytes (Handa et al, 2006;Ishiwatari et al, 2007), in human dermal fibroblasts (Carvalho et al, 2012), in human hepatoma HepG2 cells (Khanal et al, 2012) and in rat pheochromocytoma (adrenal) PC12 cells (Egawa et al, 2012). However, all these studies were carried out at high doses of parabens in the 100 μM or above range, which are well above any concentrations measureable in human breast tissue (Barr et al, 2012).…”
Section: Hallmark 3: Resisting Cell Deathmentioning
confidence: 99%
“…Other studies confirmed the low toxicity of parabens as well, including that of Soni, Carabin, and Burdock (2005) who showed that methyl and propylparaben at the concentrations of 0.25% and 0.05%, respectively, did not induce hemolysis in human and rabbit erythrocytes. In contrast, Carvalho et al (2012) evaluated the potential of some preservatives for the induction of apoptosis, necrosis, and genotoxicity against HDF cells (human fibroblasts) following the 24hours of exposure. Their results showed that methyl and propylparaben have increased genotoxic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Utility of the γH2AX assay has been also tested in the assessment of genotoxic properties of agents used to manufacture plastics and epoxy resins such as bisphenol A and bisphenol F, 167 ubiquitous pollutants such as polycyclic aromatic hydrocarbons, 168 the non-ionic surfactans nonylphenol polyethoxylates that are widely used for industrial and household purposes, 169 potential genotoxins in cosmetic preservatives, 170 or several different pharmaceuticals frequently detected in freshwater environment. 171 …”
Section: Dna Damage Signaling (Dds) Detected and Measured In Indimentioning
confidence: 99%